The other emptiness: rethinking the Zhentong Buddhist discourse in Tibet - Sheehy, Michael R.; Mathes, Klaus-Dieter (SUNY Press, 2019)
"The Other Emptiness presents a new vision of the Buddhist history and philosophy of emptiness in Tibet. The Other Emptiness brings together for the first time a collection of seminal essays by leading international Tibetan studies scholars on the subject of zhentong or "other-emptiness." This book addresses important topics in the history, literature, and philosophy of emptiness that have contributed to zhentong thinking in Tibet from the thirteenth century until today"--